BUILDING AN EFFECTIVE BUSINESS INTELLIGENCE SYSTEM TO SUPPORT STRATEGIC DECISION MAKING AT PT SHOPEE INTERNATIONAL INDONESIA - Annuri, Dina Fitria; Faeni, Bsc., MBA , Dr. Dewi Puspaningtyas (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
In today's digital age, data is a crucial asset for companies to enhance performance and support strategic decision-making. PT Shopee International Indonesia, as one of the leading e- commerce companies in Indonesia, requires an effective business intelligence system to process and analyze complex and abundant data. This system must be able to provide relevant and accurate information to stakeholders to support sound strategic decision-making that positively impacts the company. This journal discusses the design and implementation of an effective business intelligence system for PT Shopee International Indonesia. The system is built using the Business Intelligence Lifecycle (BIL).